The cascade of care in testing and treatment of latent tuberculosis infection in liver transplant candidates. Issue 1 (22nd December 2022) - Foppiano Palacios, Carlo; Medvedeva, Natalia; Cheung, Harry; Cohen, Elizabeth; Azar, Marwan M.; Malinis, Maricar
Abstract: Background: Testing and treatment for latent tuberculosis infection (LTBI) can mitigate risk of active tuberculosis (TB) post‐liver transplant (LT). Testing and treatment completion rates have been reported low in this population. Our study aims to quantify the proportion of LT candidates who completed LTBI care cascade in our center. Methods: A retrospective chart review was conducted on LT candidates from 2012 to 2021. Primary outcome was the proportion of patients who completed each cascade stage. Secondary outcome was an analysis of factors associated with positive and indeterminate LTBI testing. Results: Of the 273 LT candidates, 265 (97.1%) were referred to transplant infectious disease (TID), 264 (96.7%) had orders for interferon‐gamma release assay (IGRA), 262 (96%) underwent TID evaluation, and 259 (94.9%) completed IGRA. Twenty had LTBI, and 18 were treatment naïve and recommended for treatment. Of the 18, 15 (83.3%) agreed to therapy, 14 (77.8%) initiated treatment, and 12 (66.7%) completed treatment. No posttransplant TB reactivation occurred. Patients born in Asia, previous incarceration, past military service, and granuloma findings on chest imaging were likely to have positive IGRA ( p  < .05). Older age and travel to TB‐endemic countries were likely to have indeterminate IGRA ( p  < .05). Indeterminate IGRAs were more common in QuantiFERON (QTF)‐Gold Plus TB (15.3%) versus QTF‐Gold TB (9.3%, p  < .001). Conclusions: High rates of LTBI testing and treatment initiation and completion can be attributed to a standardized process that includes TID evaluation. Future studies in larger cohort are needed to better understand factors that can optimize the completion rates of LTBI treatment in LT candidates. Abstract :